Effect of three tandem cylinder diameter difference on flow-induced vibrations and heat transfer. (15th December 2022) - Khan, Hamid Hassan; Islam, Md.; Fatt, Yap Yit; Janajreh, Isam; Alam, Md. Mahbub
Highlights: The flow-induced vibration of three heated cylinders of unequal diameter in tandem has been investigated for the first time. The numerical analysis reveals that the increase in diameter difference between cylinders suppresses the vibration and enhances the heat transfer. The present flow configuration could envisage the design of heat exchanger tubes to reduce FIV and enhance heat transfer. Abstract: The effect of diameter differences of three tandem cylinders on flow-induced vibrations (FIVs) and convection heat transfer characteristics is investigated. The diameter reduction ratios are 0, 0.2, and 0.4, and the cylinder gap ratios are 2 and 4. The simulation is performed at Reynolds number 100, Prandtl number 0.7, reduced velocity 2 - 20, and mass ratio 2. The effect of the diameter reduction ratio on FIVs and heat transfer characteristics is observed through flow structures, oscillation amplitude, shedding frequency, correlation between lift coefficient and cylinder displacement, and Nusselt number. The flow around the downstream cylinder and the associated heat transfer depend strongly on the diameter reduction ratio. The FIV of the downstream cylinder is reduced with the increase in diameter reduction ratio. Indeed, for diameter reduction ratio 0.4 and gap ratio 2, the maximum oscillation amplitude is reduced by 48%. This is because the unequal diameter results in a weaker correlation between lift force and oscillation, modulated oscillation of cylinder, and distribution of primary shedding frequency energy to secondary frequency. At the initial and upper branches of vibration, the heat transfer from the downstream cylinder is enhanced with an increase in diameter reduction ratio due to more exposure to flow and the impingement of the gap vortices. The present flow configuration unveils reduced FIV and enhanced heat transfer, which is a desirable characteristic of multiple heated tubes for structural durability and better performance. Graphical Abstract: Image, graphical abstract